(In)visible cinemas: Reusing archival footage in Latin American cinema - Tadeo Fuica, Beatriz and Barrow, Sarah (New Cinemas: Journal of Contemporary Film, 2015)
Abstract
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9uY2luLjEzLjEuM183